Application of Intelligent Label in Monitoring the Physical and Chemical Quality of Mango Manaliga (Mangifera Indica L) - Rina Ningtyas; Pazri Gunawan; Muryeti Muryeti; Saeful Imam (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2022)
This study aimed to produce color indicator labels to determine changes in the physical and chemical quality of mangoes such as weight loss, total dissolved solids, vitamin C content during the ripening process at room temperature (±26oC), and determine the optimal storage time for viable mangoes. consumed. Measurements were made on Manalagi mango. The method used was a 2 factorial Completely Randomized Design (CRD), with variations of ammonium molybdate and chitosan. Each mango group was observed twice a day during storage at room temperature until the 10th day. The results showed that ammonium molybdate, potassium permanganate and chitosan could produce color indicator labels but did not change color during storage. The decrease in fruit quality during storage can be seen from the increasing weight loss percentage value, this is evidenced by the highest average SBK percentage value of S4 of 15.147% on the 10th day of storage. The increase in weight loss was caused by respiration and transpiration events in mangoes. The value of total dissolved solids increased until the peak of maturity occurred on the 4th day with the highest value of 11.50 oBrix and the lowest of 9.50 oBrix and then decreasing. The value of vitamin C levels increased until the 4th day of storage with the highest vitamin C content value of 34.32 mg/100g at P1 and the lowest being 24.64 mg/100g. It concluded that the optimal storage time for mangoes that are still fit for consumption is up to the 4th day of storage.